Epidemiological contemplation for a currently pragmatic COVID-19 health passport: a perspective - Ambalavanan, Radha; Snead, R Sterling; Marczika, Julia; Malioukis, Alex (Frontiers in Public Health, 2024)
The coronavirus disease 2019 (COVID-19) has caused a global pandemic that has wreaked havoc on the lives of millions of people around the world. Confinement measures aim to reduce the epidemic's spread and minimize the burden of morbidity and mortality. In response to the challenges caused by the pandemic, digital health passports have been developed exponentially. We highlight the latent epidemiological barriers to health passports to achieve standardized digital care platforms. This review paper not only highlights the epidemiological barriers but also articulates the possible infrastructure required to make the International Standard for a multi-factor authenticated and validated health passport.